Undifferentiated Connective Tissue Disease: A Case Report - Ali Aydeniz; Özlem Altındağ; Savaş Gürsoy (Archives of Rheumatology, 2009)
Undifferentiated connective tissue diseases (UCTD) are heterogeneous disorders characterized by a wide variety of signs and symptoms. Approximately 30% of cases of the disease will evolve to defined connective tissue disease; however, 70% will maintain an undifferentiated clinical course or go to complete remission. The most characteristic symptoms of UCTD present in the form of arthralgias, arthritis and Raynaud’s phenomenon. The definite classification criteria to identify UCTD are not yet available. Although these conditions are generally benign, an evolution to connective tissue diseases may occur; therefore, a regular follow-up of the patients is strongly advised. We report a case that remained undifferentiated for seven years and responded well to preventive measures and disease-modifying antirheumatic drug therapy. (Turk J Rheumatol 2009; 24: 56-7)